A Cross-Cultural Study of Pragmatic Awareness in Using Request Strategies among Merchant Marine Cadets (The Journal of Educational Development, 2021)
As an English learner, a cadet will become a seafarer that supports a global labor market for the increasing worldwide merchant shipping. This study is intended to analyze the pragmatic awareness of the cadets by examining the degree to which they recognize the request strategies they use. This study is a case study that allows the researcher to describe and examine the pragmatic awareness of request strategies between two groups of cadets: pre- and post-sea project cadets. The subject of the study was purposefully selected to get the data required. Three instruments would be used to obtain the data: a discourse completion task (DCT), a questionnaire, and, an interview guideline. The result shows that pre-sea project cadets used more direct requests compared to post-sea project cadets. Most cadets from the two groups used Category IV Strategy 8, which includes imperative and elliptical phrases. It happened because they must work in a hierarchical manner. This study is expected to involve additional variables for further study.